Deciphering transmissivity and hydraulic conductivity of the aquifer by vertical electrical sounding (VES) experiments in Northwest Bangladesh - Sattar, Golam Shabbir (Springer International Publishing, 2016)
The vertical electrical soundings (VESs) are carried out in 24 selective locations of Chapai-Nawabganj area of northwest Bangladesh to determine the transmissivity and hydraulic conductivity of the aquifer. Initially, the transmissivity and hydraulic conductivity are determined from the pumping data of nearby available production wells. Afterwards, the T and K are correlated with geoelectrical resistance and the total resistivity of the aquifer. The present study deciphers the functional analogous relations of the geoelectrical resistance with the transmissivity and the total resistivity with the hydraulic conductivity of the aquifer in northwest Bangladesh. It has been shown that the given equations provide reasonable values of transmissivity and hydraulic conductivity where pumping test information is unavailable. It can be expected that the aquifer properties viz. transmissivity and hydraulic conductivity of geologically similar area can be determined with the help of the obtained equations by conducting VES experiments.